Maximizing Tableau Server - Sarsfield, Patrick; Locker, Brandi; Mico, Adam (Packt Publishing, 2021)
Enhance the way you use Tableau Server's analytical tools by learning how to manage content to drive user engagement Key Features Understand how to quickly get connected, start publishing workbooks, and adjust basic settings Navigate the Tableau Server interface to filter and locate content, customize viewing options, and automate various tasks Learn best practices for improving the efficiency of workbooks and data sources Book Description Tableau Server is a business intelligence application that provides a centralized location to store, edit, share, and collaborate on content, such as dashboards and curated data sources. This book gets you up and running with Tableau Server to help you increase end-user engagement for your published work as well as reduce or eliminate redundant tasks. You'll explore Tableau Server's structure and how to get started by connecting, publishing content, and navigating the software interface. Next, you'll learn when and how to update the settings of your content at various levels to best utilize Tableau Server's features. You'll understand how to interact with the Tableau Server interface to locate, sort, filter, manage and customize content. Later, the book shows you how to leverage other valuable features that enable you and your audience to share, download, and interact with content on Tableau Server. As you progress, you'll cover principles to increase the performance of your published content. All along, the book shows you how to navigate, interact with, and use Tableau Server with the help of engaging examples and best practices shared by recognized Tableau professionals. By the end of this Tableau book, you'll have a solid understanding of how to use Tableau Server to manage content, automate tasks, and increase end-user engagement. What you will learn Get well-versed in Tableau Server's interface to quickly and easily access essential content Explore the different types of content and navigate through the project hierarchy quickly Understand how to connect, publish, manage, and modify content on Tableau Server Discover how to share content and collaborate with others Automate tedious tasks by creating custom views, alerts, subscriptions, and data refresh schedules Build data visualizations using Web Edit Understand how to monitor disparate metrics on multiple dashboards Who this book is for This Tableau software book is for BI developers, data analysts, and everyday users who have access to Tableau Server...